Biomechanical comparison between concentrated, follower, and muscular loads of the lumbar column. Issue 135 (October 2016) - Shih, Kao-Shang; Weng, Pei-Wei; Lin, Shang-Chih; Chen, Yi-Tzu; Cheng, Cheng-Kung; Lee, Chian-Her
Highlights: The effects of the concentrated, follower, and muscular loads on the lumbar biomechanics during flexion were numerically compared using finite-element method. The load-related effect on the lumbar rather to calculate the physiological loads of the lumbar. The kinematic and mechanical constraints significantly affect the profile, stress, and loads of the three modes. Abstract: Experimental and numerical methods have been extensively used to simulate the lumbar kinematics and mechanics. One of the basic parameters is the lumbar loads. In the literature, both concentrated and distributed loads have been assumed to simulate the in vivo lumbar loads. However, the inconsistent loads between those studies exist and make the comparison of their results controversial. Using finite-element method, this study aimed to numerically compare the effects of the concentrated, follower, and muscular loads on the lumbar biomechanics during flexion. Two conditions of equivalent and simple constraints were simulated. The equivalent condition assumes the identical flexion at the L1 level and loads at the L5 level for the three types of loads. Another condition is to remove such kinematic and mechanical constraints on the lumbar. The comparison indices were flexed profile, distributed stress, and transferred loads of the discs and vertebrae at the different levels. The results showed that the three modes in the equivalent condition show the nearly same flexed profiles. In the simple condition, however, the L1 vertebra of the concentrated mode anteriorly translates about 3 and 5 times that of the follower and muscular mode, respectively. By contrast, the flexion profiles of the follower and muscular are comparable. In the equivalent condition, all modes consistently show the gradually increasing stress and loads toward the caudal levels. The results of both concentrated and muscular modes exhibit the quite comparable trends and even magnitudes. In the simple condition, however, the removal of flexion and load constraints makes the results of the concentrated mode significantly different from its counterparts. In both conditions, the predictedindices of the follower mode are more uniform along the lumbar. In conclusion, the kinematic and mechanical constraints significantly affect the profile, stress, and loads of the three modes. In the equivalent condition, the concentrated mode can simulate the similar results to the muscular mode and top-loading fashion seems to be more practicable for experimental setup. In the simple condition, the follower mode can serve as the alternative to avoid the unreasonably higher flexion at the L1 level and shear at the L5 level. In the future, the detailed studies about the load-related effects on both load-transferring mechanism and failure mode of the lumbar-implant construct should be conducted.